Sustainability as Empty Signifier: Its Rise, Fall, and Radical Potential. Issue 1 (9th June 2015) - Brown, Trent
Abstract: Until recently, the concept of "sustainability" appeared to occupy a central position in the politics of many Western democracies. Following the 2008 financial crisis, however, sustainability has been relegated to a position of secondary or tertiary significance. This article considers the rise and fall of sustainability through the theoretical lens of Ernesto Laclau, considering whether it may be seen as an example of an "empty signifier". Through detailed engagement with Laclau's work, as well as both theoretical and empirical studies of the concept of sustainability, I argue that sustainability signifies the multiple failures of dominant discourses to recognise "the future" as a meaningful category. After examining the historical conditions under which sustainability was able to operate in this way, I go on to argue that the global financial crisis and neoliberalism more broadly have interrupted our capacity to think about the future, undermining the significance of sustainability, at least temporarily.